Analysis of Working Capital Management Against Profitability At Cv. Dalvyn Photo Studio - Aulia, Aulia; Syah, Firman; Hidayat, M. (INVOICE : JURNAL ILMU AKUNTANSI, 2022)
This study aims to determine the efficiency of the use of working capital on the profitability of CV. Dalvin Photo Studio. The research method used is descriptive quantitative method. The results of calculations in the company for three years have increased in income and also its total assets indicate that the company is quite liquid in carrying out its activities. With the increase in working capital, the company's profitability also increases or the proposed hypothesis is accepted.